Cross-Border Mergers as Instruments of Comparative Advantage. - Neary, J (Blackwell Publishing, 2007)
A two-country model of oligopoly in general equilibrium is used to show how changes in market structure accompany the process of trade and capital-market liberalization. The model predicts that bilateral mergers in which low-cost firms buy out higher-cost foreign rivals are profitable under Cournot competition. As a result, trade liberalization can trigger international merger waves, in the process encouraging countries to specialize and trade more in accordance with comparative advantage. With symmetric countries, welfare is likely to rise, though the distribution of income always shifts towards profits.